Giving hope to rural women with obstetric fistula in Ethiopia (The World Health Organization, 2013)
The world is more aware of the problem of obstetric fistula thanks to the work of Catherine Hamlin. The Australian gynaecologist and obstetrician talks to Fiona Fleck.